Pengaruh Profitabilitas Terhadap Pengungkapan Sustainability Report dengan Kepemilikan Manajerial Sebagai Variabel Moderating - Riska Fadhilah (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of profitability on the disclosure of sustainability reports moderated by managerial ownership. The population in this research is public go public listed on Indonesia Stock Exchange (IDX) during period of 2012 until 2016. The sample in this research is determined based on purposive sampling which produce 8 sample company. The nature of quantitative data and data types use secondary data obtained from www.idx.co.id, www.ncsr.com, and company website. Methods of data analysis in research used is linear regression and the difference of absolute value. The test results show that profitability has no significant positive effect on disclosure of sustainability report with significance level of 0.421 < 0.05. Managerial ownership is proxied by factor scores that can strengthen the relationship between profitability to disclosure of sustainability report with a significance level of 0.018 < 0.05, so managerial ownership is a quasi moderator variable.